Metabolic parameters on baseline 18F-FDG PET/CT are potential predictive biomarkers for immunotherapy in patients with head and neck squamous cell carcinoma - Kwon, Hye Ryeong; Cho, Junhun; Park, Sehhoon; Lee, Se-Hoon; Ahn, Myung-Ju; Choi, Joon Young; Lee, Kyung-Han; Jung, Hyun Ae; Moon, Seung Hwan (Frontiers in Medicine, 2022)
Purpose: We evaluated baseline 18F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) metabolic parameters for predicting prognosis in patients with head and neck squamous cell carcinoma (HNSCC) who were receiving immune checkpoint inhibitors (ICIs). In addition, we also investigated the relationships between immunohistochemical (IHC) biomarkers and metabolic parameters. Materials and Methods: A total of 39 patients with HNSCC who underwent 18F-FDG PET/CT prior to ICI therapy between November 2015 and December 2020 were enrolled. PET parameters of tumor lesions included standardized uptake values, metabolic tumor volume (MTV), total lesion glycolysis (TLG), and spleen-to-liver ratio (SLR). Clinical variables, IHC markers, and derived neutrophil-to-lymphocyte ratio (dNLR) were also obtained. Analysis was performed using Cox proportional hazard model, Kaplan-Meier method with log-rank test, and Spearman’s correlation. Results: Total MTV (TMTV), total TLG (TTLG), and a combined parameter consisting of TMTV and dNLR were significant predictors for progression-free survival (PFS) in univariable analysis (TMTV, p=0.018; TTLG, p=0.027; combined parameter, p=0.021). Above all, the combined parameter was an independent prognostic factor for PFS in multivariable analysis. The group with low TMTV and low dNLR had longer PFS than the group with high TMTV and high dNLR (p=0.036). SLR was the only significant predictor for overall survival (p=0.019). Additionally, there was a negative correlation between programmed cell death-ligand 1 expression (one of the IHC markers) and MTV in subgroup analysis. Conclusion: PET parameters on baseline 18F-FDG PET/CT were predictive biomarkers for prognosis in patients with HNSCC undergoing ICI therapy. With dNLR, more accurate prognostic prediction could be possible.